Relationship between Incidence of Cephalosporium Stripe and Yield Loss in Winter Wheat - M. C. Quincke; C. J. Peterson; C. C. Mundt (International Journal of Agronomy)
Cephalosporium stripe (caused by Cephalosporium gramineum) can be a serious disease of winter wheat (Triticum aestivum L.) in the Pacific Northwest of the USA. Effects of Cephalosporium stripe on yield, test weight, protein, and kernel characteristics were examined using 12 winter wheat varieties in field plots inoculated and not inoculated with the pathogen. Averaged over varieties, inoculation decreased yield, test weight, kernel weight, and kernel diameter; grain protein and the standard deviations of kernel weight and kernel diameter were increased by inoculation. Grain yield of the susceptible check was reduced by as much as 41% with addition of inoculum. The most resistant and the most susceptible varieties performed similarly for yield in the two environments, while varieties with intermediate levels of resistance were sometimes inconsistent. There was a linear relationship between yield and % whiteheads (sterile heads caused by disease) in one environment and a curvilinear relation in the other.